FUNDAMENTALS OF ACOUSTICS. THE USE OF SOUND IN MEDICINE (Journal of Universal Science Research, 2024)
This article examines the fundamentals of acoustics and their application in modern medicine. It explains the basic principles of sound, including wave propagation, frequency, and intensity, and explores their medical uses, such as diagnostic imaging, therapy, and surgical interventions. Designed for medical students, this article bridges the gap between physics and clinical practice, emphasizing the importance of acoustics in enhancing patient care.